Effect of glucosinolate of mustard-and rapeseed oil-cake on performance of crossbred cattle - TYAGI, A K; SINGHAL, K K (The Indian Journal of Animal Sciences, 2014)
Rumen fermentation of substrate was not affected by the level of glucosinolates (extracted from mustard-cake) in vitro as indicated by the concentration of several ,inetabolites, and gas production. In an another experiment, 18 crossbred males calves were distributed in 3 groups and groundnut-cake (GNC) in concentrate mixture of control group was replaced with mustard-cake(MC) and rapeseed-cake (RSC) on isonitrogenous basis. Growth performance, feed conversion efficiency and nutrient utilization were studied during 35 weeks of experimental feeding. Though the growth rate and feed efficiency were higher in GNC group than those in MC and RSC groups but variation among the groups were not significant. The dry matter intake and digestibility coefficients of proximate principles and cell wall constituents did not vary significantly among the groups.